2019
DOI: 10.1111/all.13974
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the induction of Th2 inflammation by group 2 innate lymphoid cells in response to prostaglandin D2 and cysteinyl leukotrienes in allergic rhinitis

Abstract: Background: Group 2 innate lymphoid cells (ILC2s) play important roles in allergic inflammation. However, their roles in the pathophysiology of allergic rhinitis (AR) are poorly understood. Objective: Prevalence of ILC2s in the inferior nasal turbinate (INT) tissues and the activating mechanisms of ILC2s were examined in patients with house dust mite (HDM)-induced AR. Methods: Eighteen patients with HDM-induced AR and 13 control subjects were recruited. Fresh INT tissues and peripheral blood mononuclear cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 53 publications
1
46
1
Order By: Relevance
“…The relationship between ILC2 cell function and PGs in allergic disease was first reported in a study showing that PGD 2 released from mast cells induced IL-13 production by ILC2 cells, via DP1 or DP2 receptors ( Figure 4) [79]. ILC2 cells obtained from the peripheral blood of patients with allergic rhinitis induced IL-5 production after stimulation by PGD 2 [80]. Furthermore, activation of DP2 receptor on human ILC2 cells induced their migration, production of type 2 cytokines, and increased expression of receptors for IL-33 and IL-25 [81].…”
Section: Type 2 Innate Lymphoid Cellsmentioning
confidence: 80%
“…The relationship between ILC2 cell function and PGs in allergic disease was first reported in a study showing that PGD 2 released from mast cells induced IL-13 production by ILC2 cells, via DP1 or DP2 receptors ( Figure 4) [79]. ILC2 cells obtained from the peripheral blood of patients with allergic rhinitis induced IL-5 production after stimulation by PGD 2 [80]. Furthermore, activation of DP2 receptor on human ILC2 cells induced their migration, production of type 2 cytokines, and increased expression of receptors for IL-33 and IL-25 [81].…”
Section: Type 2 Innate Lymphoid Cellsmentioning
confidence: 80%
“…In the murine model, IL‐13 produced by ILC2s caused pulmonary fibrosis under long‐term IL‐25 stimulations. In the human airway context, strong ILC2 effects in response to IL‐25 were observed in the nasal polyps of patients with CRSwNP 43,45 . Increased ILC2 frequencies and activities in response to IL‐25 are inhibited by glucocorticoid treatments via MEK/JAK‐STAT signal pathways in patients with asthma 44 .…”
Section: Epithelium‐derived Il‐25mentioning
confidence: 99%
“…Group 2 innate lymphoid cells (ILC2s) appear to be critical for allergic diseases in innate immune responses . Tissue‐resident ILC2s produce the Th2 cytokines IL‐5 and IL‐13, which are activated by prostaglandin D2 (PGD2)—chemoattractant receptor homologous molecule expressed TH2 (CRTH2) cells and cysteinyl leukotriene (cysLTs)—cysLTs receptor (CysLT1) axes . A murine study showed that IL‐33 mediates the production of IL‐5 mostly through innate activation of ILC2s, which promotes acute reactive eosinophilopoiesis in the bone marrow following exposure to airborne allergens .…”
Section: Mechanismsmentioning
confidence: 99%
“…54,55 Tissue-resident ILC2s produce the Th2 cytokines IL-5 and IL-13, which are activated by prostaglandin D2 (PGD2)-chemoattractant receptor homologous molecule expressed TH2 (CRTH2) cells and cysteinyl leukotriene (cysLTs)-cysLTs receptor (CysLT1) axes. 56 A murine study showed that IL-33 mediates the production of IL-5 mostly through innate activation of ILC2s, which promotes acute reactive eosinophilopoiesis in the bone marrow following exposure to airborne allergens. 57 Decreased number of ILC2s are observed in peripheral blood after nasal allergen challenge (NAC) and are positively correlated with AR symptoms in birch allergic objects irritated outside of the local birch pollen season.…”
Section: Environmental Factorsmentioning
confidence: 99%